Stock Assessment of The African Moony Fish (Monodactylus Sebae) (Cuvier, 1829) in The New Calabar, Nigeria - olaniyi alaba Olopade (Hasanuddin University, 2022)
Some important information on the population biology and stock assessment of African moony fish (Monodactylus sebae) was scrutinized based on monthly length frequency data collected from New Calabar River, Nigeria from February 2020 to March 2021. The estimated von Bertalanffy growth parameters were growth performance index 2.91 per year, asymptotic length (L∞) and growth curvature (K) were 36.54 cm and 0.61yr-1 respectively. The estimated theoretical age at birth (to) and longevity for the assessed fish species were 0.55 years and 2.91 years, respectively. The total mortality (Z), natural mortality (M), fishing mortality (F), for M. sebae were 1.87 year-1, 1.23 year-1 and 0.64 0.64 year-1 respectively. The length at first capture (Lc) was 8.56cm. The exploitation rate (E) and maximum exploitation rate (Emax) were calculated as 0.34 and 0.36 respectively. The recruitment pattern occurs throughout the year, with only one recruitment peaks in May with 19.9 % recruits. Biological reference points: Emsy which depicts exploitation rate producing maximum yield of a cohort indicated that, the exploitation rate which maximizes yield per recruit produced values of Emax was 0.36 while E50 was 0.23 for M. sebae indicates that the current exploitation rate was below the maximum sustainable yield, indicating that this stock was underexploited